Interactions of the Cerrado Palms Butia paraguayensis and Syagrus petraea with Parasitic and Pollinating Insects - Ilse Silberbauer-Gottsberger (Universidade Estadual de Feira de Santana, 2013)
The two cerrado palms Butia paraguayensis and Syagrus petraea were studied with regard to parasitizing and pollinating insects that visit their reproductive organs. At the study site in Botucatu, São Paulo State, both species occurred together, while at the study site in Indianópolis, Minas Gerais state, only S. petraea was growing. Bees of the subfamily Meliponinae and Halictinae were the main pollinators of B. paraguayensis and several beetles and flies were additional pollinators. The visiting beetles divided up in more exclusive parasites, such as the weevils Tripusus leiospathae and Petalochilus lineolatus, and the Colydiidae Bitoma palmarum, which bored and oviposited the closed spathe and whose larvae fed on the flower buds, as well as species of the weevil Microstrates, which bred in staminate flowers. Differently, the curculionids Anchylorhynchus bicolor, Parisoschoenus sp., Dialomia sp., and species of Mystrops (Nitidulididae) behaved as parasites and pollinators. On the other hand, S. petraea shows more evident adaptations for pollination by beetles. This species has Trigona spinipes as prominent bee pollinator, but otherwise beetles dominated as visitors, being them either parasites, pollinators or both. Although several identical beetle genera occur on both palms, at the species level they are different, as for example Anchylorhynchus camposi on S. petraea. At the two distant study sites of S. petraea in Botucatu and Indianópolis, several species, especially of the parasitic insects, are identical, indicating that parasitism is a stronger bond than pollination in this species which is characterized by a generalist pollination mode.